Analisis Peramalan Nilai Ethereum Menggunakan Model Autoregressive Integrated Moving Average - Liunardo, Nycholas; Gunawan, Didik; Murniati, Neni (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2023)
The purpose of this study is to test the ability of the Autoregressive Integrated Moving Average (ARIMA) model to predict the Ethereum value which fluctuates greatly due to the Rusian and Ukraine War. The population in this study is daily closing price data for the period May 2021 to May 2022, so the sample in this study is 396 data time series data. The results showed that the best ARIMA model for predicting the Ethereum value was ARIMA (1,1,0). ARIMA (1,1,0) can predict the Ethereum value pretty good because the value of the forecasting results is not much different from the actual value. This is also evidenced by the results of the accuracy test using MAPE which has a result of 0,448 which means the accuracy of forecasting is 55,2%.